1990
DOI: 10.1007/bf01658680
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Savary‐Gilliard and balloon dilatation of benign esophageal strictures

Abstract: The efficiency and safety of the 2 most commonly used endoscopic dilators, Savary-Gilliard and pressure balloons, were compared in 2 groups, each including 30 patients, with benign esophageal strictures. Four additional patients with tight and tortuous cervical esophageal strictures were initially managed by balloon dilatation followed by Savary-Gilliard dilatation. These patients could not be dilated by each of the methods alone. Sixty patients [35 males and 25 females with a mean age of 52 years (range, 4-91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 12 publications
0
34
0
1
Order By: Relevance
“…This result suggested that the gastroesophageal reflux is associated with anastomotic stenosis. All cases of stenosis required one or two endoscopic dilations and did not show any recurrence [17,18]. However, further clinical observation and prospective controlled studies are needed to elucidate the development of anastomotic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that the gastroesophageal reflux is associated with anastomotic stenosis. All cases of stenosis required one or two endoscopic dilations and did not show any recurrence [17,18]. However, further clinical observation and prospective controlled studies are needed to elucidate the development of anastomotic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our "technical failures" had all been surgical or endoscopic "failures" prior to referral for radiological dilatation, and several "failed" surgical and endoscopic dilatations were managed successfully by radiologically guided balloon dilatation. All methods of dilatation of GIT strictures seem to be similar in efficacy [18,19]. Some authors claim that balloon dilatation gives longer lasting symptom relief than bougienage [20], but the real bonus of balloon dilatation is its relative safety, thought to be due to the manner in which the dilating force is exerted radially on the stricture [15].…”
Section: Discussionmentioning
confidence: 96%
“…Balloon dilatation on the other hand usually requires only one passage of a balloon catheter for radiological dilatation. Some stenoses may require dilatation with an angioplasty balloon at first; however, such fight strictures are unlikely to be amenable to dilatation by any method other than a radiologically guided one [14,19]. Endoscopic balloon dilatation is now being performed increasingly frequently using "through the scope" pneumatic balloons, enabling the procedure to be performed with just one intubation [2,4].…”
Section: Discussionmentioning
confidence: 98%
“…Frequency of benign strictures at the esophagojejunostomy site ranges from 1.2% to 7.9% [7][8][9][10][11][12][13]. Although both fixed-diameter/ push-type dilators and balloon dilators give good results [14][15][16], balloon dilators are theoretically safer because push dilators exert longitudinal shearing forces in addition to radial forces [17], and also because the area can be directly visualized endoscopically during balloon dilation.Although balloon dilations are often performed with good results [9,14,15,[18][19][20][21][22][23], outcomes of through-thescope balloon dilation (TTS-BD) are uncertain because benign esophageal strictures have various causes, including reflux and radiation esophagitis [15,20,23], caustic damage [20,21,23], sclerotherapy [21], Schatzki rings [15], and surgical anastomoses [9,[18][19][20][21][22][23]. For the latter, the…”
mentioning
confidence: 99%
“…Although balloon dilations are often performed with good results [9,14,15,[18][19][20][21][22][23], outcomes of through-thescope balloon dilation (TTS-BD) are uncertain because benign esophageal strictures have various causes, including reflux and radiation esophagitis [15,20,23], caustic damage [20,21,23], sclerotherapy [21], Schatzki rings [15], and surgical anastomoses [9,[18][19][20][21][22][23]. For the latter, the…”
mentioning
confidence: 99%